The resolution revolution in cryoEM requires high-quality sample preparation: a rapid pipeline to a high-resolution map of yeast fatty acid synthase. (2020) - Joppe, Mirko; D'Imprima, Edoardo; Salustros, Nina; Paithankar, Karthik S.; Vonck, Janet; Grininge, Martin; Kuhlbrandt, Werner
No abstract available